Technological strategies aimed at fall prevention in hospital environments: an integrative review - Alves, Renata Camargo [UNESP]; Colichi, Rosana Maria Barreto [UNESP]; Lima, Silvana Andrea Molina [UNESP] (Univ Fed Sao Paulo, Dept Enfermagen, 2023)
Objective: To identify the knowledge produced about technological strategies aimed at fall prevention of adults in hospital environments. Methods: This is an integrative literature review conducted in the Medical Literature Analysis and Retrieval System Online/National Library of Medicine (MEDLINE/PubMed), Cumulative Index to Nursing and Allied Health Literature (CINAHL), Latin American and Caribbean Literature in Health Sciences (LILACS), Scopus and Web of Science databases published from 2017 to 2022. Results: A total of 19 articles were included, most of them published in nursing journals (42%). The themes that emerged from the analysis were: types of technological strategies, costs, patient privacy and nursing professionals' relevance in device development, assessment and use. Conclusion: The research revealed a range of technological resources aimed at fall prevention available in the market that can be incorporated into care practices. Hospitals must define which strategy applies most appropriately to their reality.
Keywords: Patient safety; Accidental falls; Technology; Hospitals; Accident prevention